High‐resolution regional climate model projections of future tropical cyclone activity in the Philippines. (7th October 2018) - Gallo, Florian; Daron, Joseph; Macadam, Ian; Cinco, Thelma; Villafuerte, Marcelino; Buonomo, Erasmo; Tucker, Simon; Hein‐Griggs, David; Jones, Richard G.
Abstract : The Philippines is one of the most exposed countries in the world to tropical cyclones. In order to provide information to help the country build resilience and plan for a future under a warmer climate, we build on previous research to investigate implications of future climate change on tropical cyclone activity in the Philippines. Experiments were conducted using three regional climate models with horizontal resolutions of approximately 12 km (HadGEM3‐RA) and 25 km (HadRM3P and RegCM4). The simulations are driven by boundary data from a subset of global climate model simulations from the CMIP5 ensemble. Here we present the experimental design, the methodology for selecting CMIP5 models, the results of the model validation, and future projections of changes to tropical cyclone frequency and intensity by the mid‐21st century. The models used are shown to represent the key climatological features of tropical cyclones across the domain, including the seasonality and general distribution of intensities, but issues remain in resolving very intense tropical cyclones and simulating realistic trajectories across their life‐cycles. Acknowledging model inadequacies and uncertainties associated with future climate model projections, the results show a range of plausible changes with a tendency for fewer but slightly more intense tropical cyclones. These results are consistent with the basin‐wide results reported in the IPCC AR5 and provide clear evidence that the findings from these previous studies are applicable in the Philippines region. Abstract : The Philippines is one of the most exposed countries in the world to tropical cyclones. Information on the effect of a changing climate on the cyclone activity is therefore vital for future planning. Such information is challenging to provide, due to the limitations of climate models to reliably represent tropical cyclones. The work presented here uses high‐resolution modelling to contribute and build the knowledge on the evolution of tropical cyclone activity in the region.